Immigration, integration and citizenship: elements of a new political demography. Issue 1 (2nd January 2022) - Favell, Adrian
ABSTRACT: A critical review of the state-of-the-art in migration studies. The paper centres on a contrast between established comparative scholarship – elaborating progressive models of immigration, integration and citizenship, that reflect the increasingly diverse, migrant-built societies of the North Atlantic West – and a new generation of work in the last decade, influenced by critical, anti-racist and decolonial theory, that rejects this 'Eurocentric' liberal democratic global order and self-image. Establishing a bridge between older neo-Weberian approaches to immigration and sovereign nation-state building and newer (or revived) Marxist-Foucauldian accounts, it accents the state-power building effects of bordering, managing and cultivating 'diverse' national populations, and its ongoing governmental categorisation of citizens and migrants, nationals and aliens, majorities and minorities, as a key feature of neoliberal 'racial capitalism'. The argument develops in relation to wanted and unwanted migration in advanced liberal democratic economies, "visible" forms of immigration versus 'middling' forms of everyday cross-border mobility, and the limits of humanitarian arguments for open borders and expansive asylum rights. The paper sketches an alternate politics to the self-legitimating 'political demography' of liberal democracy, relating the ongoing colonial power of ideas of immigration, integration and citizenship, to the reproduction of massive global inequalities between 'the West and the Rest'.